Kompas Digital News Kesatuan Dan Keterpaduan Komdigi Peringatan Kepada Tiktok Dan Roblox Untuk Membatasi Akun Anak-Anak - Astri Rahmah Aulia; Nurlela; T. Thyrhaya.Zein (Stilistika: Jurnal Pendidikan Bahasa dan Sastra, 2026)
Discourse analysis of popular news is a crucial step in understanding the comprehensibility of information in mass media. This study analyzes the formal and semantic aspects of a news article titled "Komdigi Peringatkan TikTok dan Roblox untuk Segera Batasi Akun Anak di Bawah 16 Tahun" (Komdigi Warns TikTok and Roblox to Immediately Limit Accounts for Children Under 16) published on Kompas.com. Utilizing the theories of Halliday and Hasan as well as Renkema, this research identifies various lingual units that function as discourse markers. The research findings reveal a dominance of grammatical cohesion, specifically references and conjunctions, which serve to connect sentences. Furthermore, the use of collocation and hyponymy was found to strengthen the lexical aspects of the text. The presence of contrastive and additive semantic relationships ensures that the discourse remains coherent. The study concludes that the appropriate use of linguistic devices significantly determines the readability of public policy news. Keywords: discourse analysis, grammatical cohesion, lexical cohesion, Kompas.com